Changing performance pressure between training and competition influences action planning because of a reduction in the efficiency of action execution - Cassell, V. E.; Beattie, S. J.; Lawrence, G. P. (Anxiety, Stress and Coping, 2018)
Background and objectives: Specificity of practice proposes optimal performance is linked to the conditions under which learning occurred. The present study investigated this effect within a pressure context to determine whether offline and/or online control processes develop specificity through the introduction or removal of performance pressure.